Shah Jahan & The Story of The Taj Mahal - Marshall, Julia (Hood Hood Books, 1996)
Shah Jahan betrayed by his own son Aurangzeb and imprisoned in a cell overlooking the Taj Mahal,the tomb of his beloveds wife,Mumtaz Mahal,recounts the story of his struggle for the throne.
Keywords: Non Fiction -Wonders of the World Book